Research handbook on EU law and human rights - Douglas-Scott, Sionaidh; Hatzis, Nicholas; Edward Elgar Publishing (Cheltenham : Edward Elgar Publishing, 2017)
The place of human rights in EU law has been a central issue in contemporary debates about the character of the European Union as a political organisation. This Research Handbook explores the principles underlying fundamental rights norms and the way such norms operate in the case law of the Court of Justice. Leading scholars in the field discuss both the effect of rights on substantive areas of EU law and the role of EU institutions in protecting them. Organised into three parts, their contributions examine the current state of the law as well as the direction of future developments in the field. The first part discusses the normative and doctrinal framework for the protection of human rights in the EU. The second part focuses on EU external relations and on the interaction between EU law and other sources of human rights rules such as the European Convention on Human Rights and international law. Finally, the third part considers the influence of human rights in areas where the EU takes action. Timely and astute, this Research Handbook will appeal to students and scholars of European law and human rights law. It will also prove a valuable and comprehensive resource for practitioners, policymakers, NGO and government officials.
Part I: The framework -- 1. Fundamental rights as a political myth of the EU: can the myth survive? / Stijn Smismans -- 2. The pluralism of European fundamental rights law / Kaarlo Tuori -- 3. The Charter of Fundamental Rights and the EU's 'creeping' competences: does the Charter have a centrifugal effect for fundamental rights in the EU? / Sybe A. de Vries -- 4. The right to move and reside: disentangling the dual dynamics of fundamental rights in EU citizenship law / Niam Nic Shuibhne -- 5. EU fundamental rights and political citizenship / Lamin Khadar -- 6. Administrative law and fundamental rights / Alexander H. Türk -- 7. EU fundamental rights and judicial reasoning: towards a theory of human rights adjudication for the European Union / Alison L. Young -- 8. Remedies under the EU Charter of Fundamental Rights / Angela Ward -- 9. EU fundamental rights in a devolved United Kingdom / Aidan O'Neill -- Part II: Beyond the European Union ---10. Fundamental rights in the European Court of Justice and the European Court of Human Rights / Marta Cartabia and Stefania Ninatti -- 11. The EU before the European Court of Human Rights after accession / Tobias Lock -- 12. Respect for human rights as a general objective of the EU's external action / Annabel Egan and Laurent Pech -- 13. Autonomy: from myth to reality - or hubris on a tightrope? EU law, human rights and international law / Katja S. Ziegler -- Part III: EU action and new directions in fundamental rights -- 14. Fundamental rights and fundamental values in the old and new Europe / Michal Bobek -- 15. Weak right, strong Court - The freedom to conduct business and the EU Charter of Fundamental Rights / Xavier Groussot -- 16. Fundamental rights in the application of competition law in the EU / Vincent Smith -- 17. The internal market and fundamental rights / Stephen Weatherill -- 18. Data protection, privacy and the foreigner / Elspeth Guild ---19. Digital freedom of expression in the EU -- Lorna Woods -- 20. The European Arrest Warrant and fundamental rights -- Massimo Fichera -- 21. Immigration, asylum and human rights in the European Union / Steven Peers -- 22. EU human rights law and environmental protection: the beginning of a beautiful friendship? / Sanja Bogojević -- 23. EU fundamental rights and the financial crisis / James Fraczyk -- 24. EU law and social rights / Sionaidh Douglas-Scott and Nicholas Hatzis -- Index
Obsahuje bibliografické odkazy a rejstřík
Elektronická reprodukce.
Keywords: Evropská unie; evropské právo; lidská práva; European law; human rights; země Evropské unie; European Union countries; e-knihy online; e-books online